2018
DOI: 10.1037/com0000105
|View full text |Cite
|
Sign up to set email alerts
|

Social basis of vocal interactions in western lowland gorillas (Gorilla g. gorilla).

Abstract: Authors have raised the possibility of identifying primitive forms of conversational rules in monkeys: temporally ruled vocal interactions, call overlap avoidance, and socially based calling partner preferences. The question as to how these abilities have evolved in the primate lineage remains open to debate, particularly because studies based on apes are scarce and controversial. We studied a captive group of western lowland gorillas and tested the influence of caller characteristics and the type of bond betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…Fifth, several studies identified conversational rules respecting key organisational properties guiding primate vocal exchanges such as turn‐taking between callers, call‐overlap avoidance and acoustic matching (e.g. Snowdon & Cleveland, ; Sugiura & Masataka, ; Lemasson, Gandon & Hausberger, ; Bouchet, Koda & Lemasson, ; Lemasson, Pereira & Levréro, ; Levréro et al ., ). For example, Levréro et al .…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%
“…Fifth, several studies identified conversational rules respecting key organisational properties guiding primate vocal exchanges such as turn‐taking between callers, call‐overlap avoidance and acoustic matching (e.g. Snowdon & Cleveland, ; Sugiura & Masataka, ; Lemasson, Gandon & Hausberger, ; Bouchet, Koda & Lemasson, ; Lemasson, Pereira & Levréro, ; Levréro et al ., ). For example, Levréro et al .…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%
“…Dunbar 36 suggested that monkey call exchanges had started to function as a mean to groom-at-distance when the size of group became too large to allocate enough time to physical grooming among all members and maintain close bonds. Indeed, "conversation-like vocal exchanges" occur mainly between two interlocutors that are determined, according to the study species, by their affiliative bonds (humans 37 ; NHP: spider monkeys Ateles geoffroyi 38 , Japanese macaques 39 , pygmy marmosets Cebuella pygmaea 6 , bonobos Pan paniscus 40 ) or by their respective ages (humans 41 ; NHP: common marmosets 42 , western lowland gorillas Gorilla gorilla gorilla 43 , Campbell's monkeys 31 ). In some cases, it was even found that human and nonhuman primates advertise this preferential bond by responding to one another using a matching acoustic structure, a phenomenon known as "vocal convergence" in ethology or "vocal accommodation" in sociolinguistics (humans 44 ; NHP: spider monkeys 38 , Diana monkeys Cercopithecus diana 45 ).…”
mentioning
confidence: 99%
“…To our knowledge, three studies have focused on vocal conversational rules in nonhuman great apes, two of which found support for turn-taking and call overlap avoidance (bonobos 40 ; gorillas 43 ), and one that did not (chimpanzees 46 ). Authors also questioned the fact that these abilities to converse in animals are genetically programmed or, as in humans 47,48 , socially acquired.…”
mentioning
confidence: 99%
See 2 more Smart Citations